Cafedrine/Theodrenaline (20:1) Is an Established Alternative for the Management of Arterial Hypotension in Germany—a Review Based on a Systematic Literature Search - Bein, Berthold; Christ, Torsten; Eberhart, Leopold H. J. (Frontiers in Pharmacology, 2017)
A 20:1 combination of cafedrine:theodrenaline (Akrinor®) is widely used in Germany for the treatment of hypotensive states during anesthesia and in emergency medicine. Although this drug formulation has been available since 1963, there are few studies relating to its use and many of the data are only available in German. In this article we summarize the available data and propose mechanisms for the effects of cafedrine/theodrenaline on cardiac muscle cells and vascular smooth muscle cells. Cafedrine/theodrenaline leads to a rapid increase in mean arterial pressure that is characterized by increased cardiac preload, stroke volume and cardiac output. Systemic vascular resistance and heart rate remain mostly unchanged. Factors which impact the effects of cafedrine/theodrenaline are gender, high arterial pressure at baseline, use of β-blockers and heart failure. Importantly, the drug is frequently used in obstetric anesthesia without detrimental effects on umbilical cord pH or APGAR score.